Role of Surgery in Liver Abscess - Abdullah,; Ahmed Qureshi, Shoaib; Zarkoon, Rehan; Bugti, Muhammad Hanif; Syed Abdul Nasir,; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2024)
Background: Liver abscesses are localized pus collections in the liver, often resulting from various infections. They pose significant clinical challenges, with the potential for severe complications and adverse outcomes. Objective: This study aims to evaluate the role of surgical interventions in the management of liver abscesses, specifically within the patient population of Bolan Medical Complex, Quetta. It seeks to analyze surgical outcomes, complications, and patient recovery in comparison to other treatment modalities. Methods: A qualitative approach was employed, involving semi-structured interviews with 100 patients who underwent surgical procedures for liver abscesses at Bolan Medical Complex. The data were analyzed to identify patterns related to surgical efficacy and patient experiences. Results: The findings indicate that open drainage remains the most performed procedure, with a high success rate of 80% in achieving favorable outcomes. Complications occurred in 15% of cases, and the average length of hospital stay varied, with half of the patients being discharged within 1-3 days post-surgery. Conclusion: Surgical intervention plays a critical role in the management of liver abscesses, particularly in cases resistant to medical treatment. The study highlights the importance of careful patient selection and the benefits of surgical procedures in improving patient outcomes and quality of life